Influence of Clay Content on Crack Evolution of Clay–Sand Mixture - Jiang, Xiangang; Huang, Qin; Zhang, Zongliang; Vallejo, Luis E.; Chen, Xiaoqing; Zhao, Wanyu; Deng, Hongyan; Liu, Xingrong; Song, Danqing; Chen, Zhuo (Frontiers in Earth Science, 2022)
Clay particles have an important influence on the cracking of clay–sand mixture, but the quantitative relationships between the clay content and crack evolution of the clay–sand mixture are still not clear. In order to explore the crack evolution process of the clay–sand mixture under different clay content conditions, we prepared nine groups of saturated clay–sand mixture samples with different clay contents and carried out drying experiments and Brazilian tests. The geometric dimensions and development forms of soil cracking were quantitatively analyzed by taking pictures of the sample cracks, image processing, and weighing the variation of the soil mass at the corresponding time during the drying process. The results showed that when the clay content was greater than 50%, the development process of the clay–sand mixture cracks can be divided into three stages: the formation stage of main cracks, the generation stage of the autonomously derived secondary fractures, and the stage of cracks widening. When it was less than 50%, the cracks in the development process of clay–sand mixture cracks had the characteristics of short length, dense crack spacing, no main cracks, and no obvious stage. The clay could add the tensile strength of the mixture and restrain crack development. The clay content had a significant effect on the shrinkage cracking and crack development process of soil, which shows that with the increase in the clay content, the tensile strength increases and restrains the crack development; the crack rate increases continuously and the width of cracks become larger; the lower the clay content, the lower is the crack rate and the smaller is the average crack width. The water content of samples with different clay soil contents all nonlinearly decreased with the increase in drying time, and the corresponding residual water content increased with the increase in the clay soil content at the same time. The water content of initial cracking, stable crack length, stable crack width, and stable block of the clay–sand mixture increased with the increase in the clay content, and the water content of the stable crack length was the same as that of the stable block number.